A Novel and Compact Metamaterial-Based Four-Element MIMO Antenna System for Millimeter-Wave Wireless Applications with Enhanced Isolation - Iftikhar Ud Din; Nisar Ahmad Abbasi; Waheed Ullah; Sadiq Ullah; Messaoud Ahmad Ouameur; Dushantha Nalin K. Jayakody (International Journal of Antennas and Propagation)
A compact fork-shaped MIMO antenna system with a 2 × 2 arrangement with four elements is presented. The MIMO elements are arranged orthogonally to achieve a small overall size of 36 × 28 mm2 and a wide bandwidth for 5G mm-wave applications. MIMO elements are positioned 4 mm from each corner of the substrate to achieve compact size and minimize coupling. To improve the isolation of the proposed MIMO system, a metamaterial slab is inserted in the middle of the substrate and between radiating elements of the MIMO antenna system, which improves isolation by 10 dB within the whole operating band and achieves maximum isolation of 65 dB at 34.5 GHz. The proposed MIMO system operates in the Ka-band frequency range of 22–50 GHz with isolation greater than 30 dB and efficiency above 80% across the entire frequency spectrum for 5G communication. Additionally, the performance parameters of MIMO are examined, including diversity gain (DG) and envelope correlation coefficient (ECC), and it is found that they meet the required standards of DG approximately equal to 10 and ECC < 0.05. The proposed MIMO system has been fabricated and tested. The measured results are consistent with the design of the simulated structure using the CST Microwave Studio (CSTMWS) simulator.